Dwelling in Political Landscapes Contemporary Anthropological Perspectives - Lounela, Anu; Berglund, Eeva; Kallinen, Timo (Studia Fennica Anthropologica, 2019)
People all over the globe are experiencing unprecedented and often hazardous situations as environments change at speeds never before experienced. This edited collection proposes that anthropological perspectives on landscape have great potential to address the resulting conundrums. The contributions build particularly on phenomenological, structuralist and multi-species approaches to environmental perception and experience, but they also argue for incorporating political power into analysis alongside dwelling, cosmology and everyday practice. The book's 13 ethnographically rich chapters explore how the material and the conceptual are entangled in and as landscapes, but it also looks at how these processes unfold at many scales in time and space, involving different actors with different powers. Thus it reaches towards new methodologies and new ways of using anthropology to engage with the sense of crisis concerning environment, movements of people, climate change and other planetary transformations. Dwelling in political landscapes: contemporary anthropological perspectives builds substantially upon anthropological work by Tim Ingold and others, which emphasises the ongoing and open-ended, yet historically conditioned ways in which humans and nonhumans produce the environments they inhabit. In such work, landscapes are understood as the medium and outcome of meaningful life activities, where humans, like other animals, dwell. This means that landscapes are neither social/cultural nor natural, but socio-natural. Protesting against and moving on from the proverbial dualisms of modern, Western and maybe capitalist thought, is only the first step in renewing anthropology's methodology for the current epoch, however. The contributions ask how seemingly disconnected temporal, representational, economic and other systemic dynamics fold back on lived experience that are materialised in landscapes.